The adoption of active methodologies and their impacts on teaching: a case study in the Faculdade Vale do Salgado – FVS (Revista Brasileira de Contabilidade e Gestão, 2019)
The development of the professional profile together with the theoretical learning constitutes a challenge for the Institutions of Higher Education. Thus, the use of Active Methodologies as an aid to conventional teaching methodologies is one of the proposals to overcome this challenge. Through these, students can enhance such characteristics as leadership and teamwork. Regarding the Professional Accountant, the labor market has required in addition to only calculating the amount to be paid in taxes, surpassing the traditional view. Business managers and Clients seek professionals who know how to explain the company's financial situation, prepare management reports and be proactive. The present study aims to verify the adoption of Active Methodologies and the impacts on teaching, through a case study carried out at the Faculdade Vale do Salgado - FVS. For this, the Faculty of Accounting Sciences answered structured questionnaires with objective and subjective questions related to the use and knowledge of the object studied. The results showed that although the teachers understood their importance, the majority of respondents use them only with monthly frequency. Although limited to the teachers, the research was not without relevance, as it showed their understanding regarding the adoption of the methodologies, as well as, pointed out the benefits perceived in the students during the classes in which they are used.
Keywords: Active Methodologies; Teachers; Accounting Sciences